Emerging trends in the new world situation - Otunnu, Olara (Round table (London), 1992)
THE AUTHOR PROPOSES TO TOUCH ON A FEW ELEMENTS, A FEW FACTORS, AND, A FEW CHALLENGES, WHICH IN HIS VIEW, CHARACTERIZES THE EMERGING WORLD SITUATION IN ITS DISORDERLINESS, IN ITS DISORIENTATION, AND IN THE COMPLEXITY WHICH IT REPRESENTS. HE EXPLORES: SOVEREIGNTY; MOUNTING INTERNAL CONFLICTS; SECOND-GENERATION SELF-DETERMINATION; COLLECTIVE SECURITY; U.S. POWER; THE MEREGING GLOBAL AGENDA; AND, SOLIDARITY.